Arbuscular mycorrhiza induces low oxidative burst in drought-stressed walnut through activating antioxidant defense systems and heat shock transcription factor expression - Ma, Wen-Ya; Qin, Qiu-Yun; Zou, Ying-Ning; Kuča, Kamil; Giri, Bhoopander; Wu, Qiang-Sheng; Hashem, Abeer; Al-Arjani, Al-Bandari Fahad; Almutairi, Khalid F.; Abd_Allah, Elsayed Fathi; Xu, Yong-Jie (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) have important roles in enhancing drought tolerance of host plants, but it is not clear whether and how AMF increase drought tolerance in walnut (Juglans regia). We hypothesized that AMF could activate antioxidant defense systems and heat shock transcription factors (Hsfs) transcription levels to alleviate oxidative damage caused by drought. The walnut variety ‘Liaohe No. 1’ was inoculated with Diversispora spurca and exposed to well-watered (WW, 75% of the maximum soil water capacity) and drought stress (DS, 50% of the maximum soil water capacity) for 6 weeks. Plant growth, antioxidant defense systems, and expressions of five JrHsfs in leaves were studied. Such drought treatment inhibited root mycorrhizal colonization, while plant growth performance was still improved by AMF inoculation. Mycorrhizal fungal inoculation triggered the increase in soluble protein, glutathione (GSH), ascorbic acid (ASC), and total ASC contents and ascorbic peroxidase and glutathione reductase activities, along with lower hydrogen peroxide (H2O2), superoxide anion radical (O2•−), and malondialdehyde (MDA) levels, compared with non-inoculation under drought. Mycorrhizal plants also recorded higher peroxidase, catalase, and superoxide dismutase activities than non-mycorrhizal plants under drought. The expression of JrHsf03, JrHsf05, JrHsf20, JrHsf22, and JrHsf24 was up-regulated under WW by AMF, while the expression of JrHsf03, JrHsf22, and JrHsf24 were up-regulated only under drought by AMF. It is concluded that D. spurca induced low oxidative burst in drought-stressed walnut through activating antioxidant defense systems and part Hsfs expressions.